Re-examining the rules of Ao-jiu in modern style poetry - Gan, Kim Soon (2019)
The theory of Ao-jiu is being questioned all these years, and even arouse controversy to overturn it frequently. It is mainly due to dissatisfaction with ‘rules of Ao-jiu using by Tang people’ which were firstly published in Shengdiao Pu by Zhao Zhi-xin from Qing dynasty, and due to existences of examples which against the theory of Ao-jiu. According to Wang Li, there are two categories of Ao-jiu: as a replacement for the tonal pattern in the same verse and as a replacement for the tonal pattern in the following pair verse. Through the literature research methodology, this study had found that the fronter’s Zi-lei-te-shi (level-level-oblique-level-oblique) is not formed by exchanging between the third and fourth character of the standard tonal pattern of ‘level-level-level-oblique-oblique’; and Gu-ping-ao-jiu (oblique-level-level-oblique-level) also not formed by exchanging between the first and third character of the standard tonal pattern of ‘level-level-oblique-oblique-level’. The fact is that these two types of tonal patterns are formed by imitate rhetoric of ancient poetry. The latter, found that either Xiao-ao (formed by changing the third character of the standard tonal pattern of ‘oblique-oblique-level-level-oblique’) or Da-ao (formed by changing the fourth character of the standard tonal pattern of ‘oblique-oblique-level-level-oblique’), both are frequently replaced by the following pair verse, using the tonal pattern of ‘level-level-level-oblique-level’ or ‘oblique-level-level-oblique-level’. Furthermore, the theory of Hu-yao can be considered as the alternate explanation for the unreplaced Xiao-ao. As a conclusion, the category to do a replacement for the tonal pattern in the following pair verse makes sense. This study also concludes that the ‘Up-support by Three Level Tones’ of the theory of ‘Support’ that comes from Shi Suinao by Yuan Jing, in early Tang dynasty actually can be considered as the origin of the category of to do a replacement for the tonal pattern in the following pair verse. This concludes the confirmation of the origin for the theory of Ao-jiu in modern style poetry. After making arrangement, twelve types of couplets are formed finally by matching between six types of first verse and two types of following pair verse. The subfinding: ‘freely first third fifth, differently second fourth sixth’ is discovered that it points to the defect of Ge-ju-shang-wei for non-rhyming works actually, and together with other explanations, a new conclusion is made that the second character and the sixth character (fourth character of 5-character poetry) of 7-character poetry actually are not the points of rhythm. Along with this subversions of ‘traditional cognitions’ upon prosody, the rationalization of the theory of Ao-jiu has got a high level of strengthening.